Hypoglycemic activity of the Anisopus mannii N. E. Br. methanolic leaf extract in normal and alloxan-induced diabetic mice. - Moses Z. Zaruwa (2018)
The hypoglycemic activities of nine sub-fractions from the methanolic leaf crude extract of Anisopus mannii were investigated in normoglycemic and alloxan-induced diabetic mice. The methanolic sub-fraction M at 400 mg/kg bw showed significantly (p<0.05) high reduction in fasting blood glucose (FBG) at 27.36 and 65.57% in normoglycemic and diabetic mice, respectively. In acute toxicity test, M at 2,000 and 5,000 mg/kg bw showed reduction in blood urea nitrogen and creatinine level, elevations in aspartate transaminase, alanine transaminase and total bilirubin levels, as well as the body weights. The weight-ratios of kidney and liver to the body weight of the mice fed with these doses of M were reduced with no sign of histopathological alteration. The M at 250 mg/kg bw significantly reduced the FBG levels in a postprandial study. The hypoglycemic effect of M was eliminated when co-administered with isosorbide dinitrate or nifedipine indicating the induction of insulin secretion via K+ ATP-dependent channels. The UV/HPLC analysis of M indicated saponin at 7.7 mg/g. This study confirmed the traditional use of A. mannii for diabetes mellitus and the potential for the further development as a novel hypoglycemic drug.